2019
DOI: 10.1016/j.seizure.2019.01.023
|View full text |Cite
|
Sign up to set email alerts
|

Seizures in Children with HIV infection in South Africa: A retrospective case control study

Abstract: A B S T R A C TPurpose: Data relating to the role that Human immunodeficiency virus (HIV) contributes towards seizures in HIV-infected children is limited. The management of seizures in this group is complex due to potential interactions between antiseizure medication and antiretroviral therapies. This study explores the seizure semiology and course of a population of affected children based on questions raised from a previous epidemiological study. Methods: A retrospective case-control study of all patients p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 27 publications
0
7
0
1
Order By: Relevance
“…As for the prevalence or incidence of epilepsy in the HIV+ population, most studies only reported the prevalence or incidence of seizures in detail, and only a few reported recurrent rates and followed up to the diagnosis of epilepsy. From the three studies reported so far, the proportion of HIV+ patients who had seizures and were subsequently diagnosed with epilepsy was very high (37/38, 21/27, and 32/52) [6,13,14]. It can be considered that the epidemiological characteristics of epilepsy in HIV+ patients may be similar to seizures.…”
Section: Epidemiological Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…As for the prevalence or incidence of epilepsy in the HIV+ population, most studies only reported the prevalence or incidence of seizures in detail, and only a few reported recurrent rates and followed up to the diagnosis of epilepsy. From the three studies reported so far, the proportion of HIV+ patients who had seizures and were subsequently diagnosed with epilepsy was very high (37/38, 21/27, and 32/52) [6,13,14]. It can be considered that the epidemiological characteristics of epilepsy in HIV+ patients may be similar to seizures.…”
Section: Epidemiological Characteristicsmentioning
confidence: 99%
“…According to the epilepsy definition by International League against Epilepsy (ILAE) in 2014 [22] and seizures classification in 2017 [23], most seizures in HIV-infected patients are generalized. The proportion of generalized seizures in patients with NOS ranged from 35.3% [12] to 67.3% [14].…”
Section: The Predilection Types and Occasions Of Seizures Or Epilepsymentioning
confidence: 99%
See 3 more Smart Citations